Promosi Popping Dance Oleh Fusion Crew Padang - Yulio Raihan Fernando; Dwi Mutia Sari (Lembaga Pengembangan Kinerja Dosen, 2023)
The design of the promotional video aims to introduce popping dance. It is hoped that it will attract the attention of dancers in the city of Padang to learn it. The problem found is that there is no next generation of popping dance in the city of Padang and no one is promoting popping dance anymore. To overcome this problem, the design method used is the 4D (four-D) method which consists of 4 stages, namely definition, design, development, and dissemination. This 4D development method and model was chosen because it aims to find the next generation of popping dance and it is hoped that dancers in the city of Padang will be interested in learning it. The results of the design of the popping dance promotional video with a duration of 4 minutes 30 seconds have been tested for its feasibility with several audiences. The main media is a popping dance promotional video as a medium to promote or introduce popping dance to the target audience. As a support, several other media such as posters, xbanners, t-shirts, stickers, lanyards, speakers, and dance floors were also designed.